Revision of the bee group Anthophora (Micranthophora) (Hymenoptera: Apidae), with notes on potential conservation concerns and a molecular phylogeny of the genus - Orr, Michael C.; Pitts, James P.; Griswold, Terry (Zootaxa, 2018)
Anthophora (Micranthophora) comprises the largest subgenus of Anthophora in the Western Hemisphere, with 26 species. Though previously synonymized with the Anthophora (Heliophila), A. (Micranthophora) is here confirmed as a subgenus, morphological and multi-gene molecular phylogenetic evidence refute this and the synonymy of A. (Micranthophora) to A. (Heliophila) is formally rejected. Characters for (Micranthophora) are given and a key to species is provided. Seven new species are described: Anthophora (Micranthophora) caudata Orr, sp. nov.; Anthophora (Micranthophora) chihuahua Orr, sp. nov.; Anthophora (Micranthophora) escalante Orr, sp. nov.; Anthophora (Micranthophora) parkeri Orr, sp. nov.; Anthophora (Micranthophora) rara Orr, sp. nov.; Anthophora (Micranthophora) striata Orr, sp. nov.; and Anthophora (Micranthophora) timberlakei Orr, sp. nov. Further, four new synonyms are enacted: A. arthuri and A. flexipes to A. albata, A. nigritula to A. exigua, and A. xanthochlora to A. pachyodonta. Distributional and phenological data, as well as known details of nesting biology and floral specialization, are provided. Future research directions and species of potential conservation interest are also discussed.